Development of Self-oscillating Human Vocal Folds Prosthesis. (2016) - Horáček, Jaromír; Bula, Vítězslav; Radolf, Vojtěch; Vampola, Tomáš; Dušková, Miroslava
Abstract: The study compares results of in vitro measurements of phonation characteristics performed on three types of originally developed 1:1 scaled artificial models of human vocal folds. The measured aerodynamic, vibration and acoustic characteristics are in good agreement with the values found in humans.